Determinants of post-stroke cognitive impairment and dementia: association with objective measures and patient-reported outcomes - Oliveira, Lara C.; Bonkhoff, Anna K.; Ponciano, Ana; Tuozzo, Carissa; Viswanathan, Anand; Rost, Natalia S.; Etherton, Mark R. (Frontiers in Stroke, 2023)
Background Post-stroke cognitive impairment and dementia (PSCID) is a sequel of ischemic stroke (IS), highly prevalent and linked to poor long-term outcomes. Thus, early recognition of the clinical determinants of PSCID is urgent for identifying high-risk individuals who are susceptible to PSCID. And investigating objective measures of PSCID in relation to patient-reported outcome measures (PROMs) is essential for understanding the impact of IS. Here we identify the clinical determinants associated with PSCID and the relationship of PSCID to patient-reported outcomes in a population with IS. Methods This was a cohort study. We enrolled 138 patients who were admitted to our hospital between February 2017 and February 2020, with IS and no pre-stroke diagnosis of dementia. Clinical variables were acquired on admission. At 3 months, patients underwent a follow-up evaluation including the Telephone Interview for Cognitive Status (TICS), modified Rankin scale (mRS), Barthel Index (BI), and PROMs, using the Patient-Reported Outcomes Measurement information System Global Health (PROMIS GH). MCI/Dementia was defined as a TICS score of <36. Regression analyses were used to identify clinical, functional, and patient-reported outcome determinants of the 3-month TICS score. Analyses were adjusted for age, stroke severity, and prior IS. Results At follow-up, 113 participants (82%) were found to have MCI/Dementia. Patients with PSCID were more likely to be older, and at 3-months post-stroke they had lower rates of PROMIS GH T Mental (mean 47.69 vs. 52.13) and T Physical (mean 46.75 vs. 50.64). In multivariable linear regression analyses, increasing age (β = −0.07, p = 0.03) and Peripheral Artery Disease (PAD; β = −3.60, p = 0.03) were independently associated with a lower TICS score. Functional and patient-reported outcomes were also associated with worse TICS, including mRS ≥ 2, BI, T Mental, Global Mental, T Physical, and Global Physical in adjusted analyses. Individual components of PROMs were also associated with TICS, including quality of life, mental health, social satisfaction, and physical activities. Conclusions In patients with IS, increased age and a pre-admission diagnosis of PAD are independently associated with worse objective measures of PSCID. Worse functional and patient-reported outcomes are also strongly linked to PSCID.